Sustainable Room-Temperature Hydrogen Sensing Based on Pristine Biomass-Derived Prosopis Africana Carbon Nanoparticles - Garba, Lurwan; Lamido Sumaila, Jamila; Olanrewaju Kayode, Yusuf; Babani, Sulaiman; Yunusa, Zainab (FUDMA Journal of Sciences, 2026)
Biomass derived materials have recently attracted significant attention as sustainable and cost-effective candidates for gas sensing applications. In this study, nanoparticles derived from Prosopis africana charcoal (PACC) were developed and investigated for hydrogen (H2) gas detection at room-temperature. The charcoal was produced from Prosopis africana stem via controlled pyrolysis at 500 °C for 3 h under limited oxygen conditions. The PACC sensing film was fabricated by blending the nanoparticles with linseed oil as an organic binder in a 40:60 wt:% ratio, followed by annealing at 500 °C for 3.5 h. The morphological and structural properties of the sensing film were characterized using field emission scanning electron microscopy (FESEM), and energy-dispersive X-ray spectroscopy (EDX). Gas sensing performance was evaluated toward hydrogen concentrations ranging from 100 to 1000 ppm at room temperature. The sensor exhibited measurable response across the tested concentration range, demonstrating the potential of PACC nanoparticles as an effective sensing material. To the best of our knowledge, this study represents the first report on room temperature hydrogen sensing using Prosopis africana charcoal nanoparticles, highlighting their promise as a low-cost and sustainable alternative for gas sensing applications.
Keywords: Hydrogen gas; gas sensor; Nanoparticles; prosopis africana